Native title, fictions and 'convenient falsehoods' - G. Nettheim (Law Text Culture, 1998)
The fiction of Australia as 'terra nullius' was officially discarded by the High Court of Australia in Mabo v Queensland (No 2) (1992), so far as the preexisting rights to land of Indigenous Australians were concerned. But an alternative fiction continues to perform a similar role, and continues to influence public discourse. It, too, would justify the continuing displacement of what may remain of Indigenous peoples' property rights. The fiction is usually expressed in the catchphrase 'land management is a prerogative of the States'. This fiction is given ample accommodation in the Native Title Amendment Bill 1997 ('the NTAB').